Detectives, dystopias, and poplit : studies in modern German genre fiction - Campbell, Bruce, 1955-; Guenther-Pal, Alison; Petersen, Vibeke Rützou, 1943- (Studies in German literature, linguistics, and culture., 2014)
The first broad treatment of German genre fiction, containing innovative new essays on a variety of genres and foregrounding concerns of gender, environmentalism, and memory.